Digital Dead-Beat and Repetitive combined control for stand-alone four-leg VSI - Lidozzi, Alessandro; Ji, Chao; Solero, Luca; Zanchetta, Pericle; Crescimbini, Fabio (IEEE, 2017)
This paper deals with a newly conceived combined control topology. Dead-Beat and Repetitive controllers are proposed to operate jointly in a 4-leg VSI for stand-alone applications. In such mode of operation, dedicated controller has to regulate the inverter output voltages, which are measured at the output of the power filter. In the proposed combined control, the Dead-Beat rapidly compensates the output voltage variations due to load changes; whereas, the Repetitive Control provides the required harmonic compensation capabilities that are mandatory to comply with the Standards, when balanced and unbalanced non-linear loads have to be fed. As a consequence, high dynamic performance is assured, as well harmonics in the output voltages are almost absent. In fact, the achieved experimental tests have verified that resulting output voltage THD is around 0.5% also in case of highly unbalanced and non-linear loads, compensating also the distortion introduced by the switches dead-time.